Comparative Outcomes of Minimally Invasive Surgery for Posterior Lumbar Fusion: A Systematic Review - Goldstein, Christina L. (Springer US, 2014)
BACKGROUND: Although minimally invasive surgical (MIS) approaches to the lumbar spine for posterior fusion are increasingly being utilized, the comparative outcomes of MIS and open posterior lumbar fusion remain unclear. QUESTIONS/PURPOSES: In this systematic review, we compared MIS and open transforaminal or posterior lumbar interbody fusion (TLIF/PLIF), specifically with respect to (1) surgical end points (including blood loss, surgical time, and fluoroscopy time), (2) clinical outcomes (Oswestry Disability Index [ODI] and VAS pain scores), and (3) adverse events. METHODS: We performed a systematic review of MEDLINE(®), Embase, Web of Science, and Cochrane Library. Reference lists were manually searched. We included studies with 10 or more patients undergoing MIS compared to open TLIF/PLIF for degenerative lumbar disorders and reporting on surgical end points, clinical outcomes, or adverse events. Twenty-six studies of low- or very low-quality (GRADE protocol) met our inclusion criteria. No significant differences in patient demographics were identified between the cohorts (MIS: n = 856; open: n = 806). RESULTS: Equivalent operative times were observed between the cohorts, although patients undergoing MIS fusion tended to lose less blood, be exposed to more fluoroscopy, and leave the hospital sooner than their open counterparts. Patient-reported outcomes, including VAS pain scores and ODI values, were clinically equivalent between the MIS and open cohorts at 12 to 36 months postoperatively. Trends toward lower rates of surgical and medical adverse events were also identified in patients undergoing MIS procedures. However, in the absence of randomization, selection bias may have influenced these results in favor of MIS fusion. CONCLUSIONS: Current evidence examining MIS versus open TLIF/PLIF is of low to very low quality and therefore highly biased. Results of this systematic review suggest equipoise in surgical and clinical outcomes with equivalent rates of intraoperative surgical complications and perhaps a slight decrease in perioperative medical complications. However, the quality of the current literature precludes firm conclusions regarding the comparative effectiveness of MIS versus open posterior lumbar fusion from being drawn and further higher-quality studies are critically required. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11999-014-3465-5) contains supplementary material, which is available to authorized users.